Amphibian occupancy and abundance in beaver ponds in Switzerland - Bolle, Patricia (Neuchâtel : Université de Neuchâtel, 2024)
As ecosystem engineers, beavers are capable of creating heterogeneous environments that have a positive impact on many species. They increase habitat availability that can be colonised by species (endangered or not) and reduce fragmentation. Amphibians, one of the most threatened groups of vertebrates, are part of the species that could use and colonise the beaver ponds. The aim of this study is to analyse the occupancy and abundance of amphibians in beaver ponds in Switzerland. This analysis addressed the following questions: 1) What is amphibian abundance and occupancy at beaver ponds, 2) Does Rana temporaria use beaver ponds as ovipositional sites, 3) What are the factors (e.g., dam age) that drive amphibian occupancy and abundance in beaver ponds, and 4) if beaver ponds increaseconnectivity. Results of the occupancy analysis revealed that there were some preferences for the type of beaver pond occupied, most of them being flooded forests. Then, results from both abundance and occupancy showed that the strongest predictor that always came up was the dam age. Indicating that the older the dam is, the better, with more individuals in middle aged dams. Results from the connectivity revealed that beaver ponds had higher diversity if there were at least two amphibian breeding ponds nearby (less than one kilometre). Meaning that beavers could extend the already existing amphibian network by creating new ponds. Consequently, they have a good potential for conservation goals by maintaining stable and increasing amphibian populations.
Keywords: Amphibians; Beaver ponds; occupancy; abundance; dam age; conservation